An analytical study on the performance of the organic rankine cycle for turbofan engine exhaust heat recovery - Saadon, S.; Abu Talib, A. R. (IOP Publishing, 2016)
Due to energy shortage and global warming, issues of energy saving have become more important. To increase the energy efficiency and reduce the fuel consumption, waste heat recovery is a significant method for energy saving. The organic Rankine cycle (ORC) has great potential to recover the waste heat from the core jet exhaust of a turbofan engine and use it to produce power. Preliminary study of the design concept and thermodynamic performance of this ORC system would assist researchers to predict the benefits of using the ORC system to extract the exhaust heat engine. In addition, a mathematical model of the heat transfer of this ORC system is studied and developed. The results show that with the increment of exhaust heat temperature, the mass flow rate of the working fluid, net power output and the system thermal efficiency will also increase. Consequently, total consumption of jet fuel could be significantly saved as well.